July 7th 2005 and its Aftermath - Chapman, Elizabeth (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
I have been asked to give an account of the effect of the London bombs in July 2005 and how UCL library Services responded. In describing UCL’s libraries I shall deal with service continuity and the effects on staff. I shall then show some of the outcomes of our subsequent review of emergency preparedness and the follow-up we have initiated. I do not intend to provide too much detail on what actually happened but will give some where it sheds light on subsequent review and planning. Despite the grim nature of these events I intend to end with an optimistic note.